Implementation of Hydrocarbon Adventures Game as An Online Learning Media During Covid-19 Pandemic - Aini, Nur Qurrotur; lutfi, achmad (JCER (Journal of Chemistry Education Research), 2023)
The purpose of this study was to determine the application of the game Hydrocarbon Adventures as an online learning medium for hydrocarbon compounds in the covid-19 pandemic. The design of this study used the one-group-pretest-posttest experimental method. The target of this research is online learning using Hydrocarbon Adventures media games conducted by 27 grade XI students of Senior High School 1 Sampang. The students will be given a pretest before using the game and post test after using it. After that, students will be given questionnaire for the learning using online learning media. The results showed that student learning outcomes after using the learning media Hydrocarbon Adventures game had increased with classical completeness for values reaching 92.59%, and an increase in student learning outcomes at an average pretest value of 44.19 into an average post test score amounting to 83.41. Student responses about game media were obtained 79.2%. Based on these results, it was concluded that the Hydrocarbon Adventures learning media on the material of hydrocarbon compounds through online learning during the covid-19 pandemic can improve student learning outcomes.The purpose of this study was to determine the application of the game Hydrocarbon Adventures as an online learning medium for hydrocarbon compounds in the covid-19 pandemic. The design of this study used the one-group-pretest-posttest experimental method. The target of this research is online learning using Hydrocarbon Adventures media games conducted by 27 grade XI students of Senior High School1 Sampang. The students will be given a pretest before using the game and post test after using it. After that, students will be given questionnaire for the learning using online learning media. The results showed that student learning outcomes after using the learning media Hydrocarbon Adventures game had increased with classical completeness for values reaching 92.59%, and an increase in student learning outcomes at an average pretest value of 44.19 into an average post test score amounting to 83.41. Student responses about game media were obtained 79.2%. Based on these results, it was concluded that the Hydrocarbon Adventures learning media on the material of hydrocarbon compounds through online learning during the covid-19 pandemic can improve student learning outcomes.